The impact of promotion on purchase intentions in Jordan: Video game industry - Ayman El-Okah; Shafig Al-Haddad; Abdel-Aziz Ahmad Sharabati (International Journal of Data and Network Science, 2023)
This study is done to identify the impact of promotion on the purchase intentions of video games in Jordan. The independent variables used to test promotion were trailers, discounts, influencers/streamers, and social media. The data were collected by using a survey designed on google forms sent or using a Quick Response (QR) code to random gamers in Jordan. 129 people responded to the survey. The data were coded on SPSS and reliability, validity, and correlation among variables were confirmed, then the hypotheses were tested by multiple regressions. The researcher found a statistically significant impact of promotional tools on purchase intentions of the video gaming industry in Jordan, where trailers have the highest significant positive effect on purchase intentions, followed by social media, then influencers/streamers, while discounts do not significantly affect purchase intentions of video games in Jordan. Some limitations and recommendations for future research have been provided at the end of the research.